Accountability for Motorized Vehicle Owners Used By Children in Traffic Accidents (Case Study on Supreme Court Decision Number 1029 K / Pid.Sus / 2015) - Yanto Risdianto; Lathifah Hanim (Jurnal Daulat Hukum, 2020)
The formulation of the problem in this study are: 1) parts of criminal liability of the owner of a motorized vehicle whose vehicle was used in a traffic accident Case Study of the Decision of the Supreme Court of the Republic of Indonesia Number 1029 K / Pid.Sus / 2015? And 2) how is the legal protection of children as perpetrators in traffic accidents Case Study of the Supreme Court's Decision No. 1029 K / Pid.Sus / 2015?The method used by researchers is juridical sociological legal approach and the specifications in this study are descriptive analytical. The sources and types of data in this study are primary data obtained from interview field studies. And secondary data obtained from literature studies relating to the theory of criminal liability and legal protection.Based on the results of that study The criminal liability of the owner of a motorized vehicle whose vehicle is used in a traffic accident by a child is not held accountable even if only as an inclusion, the child who commits a traffic violation or a traffic crime is the sole offender, even if the motorized vehicle used by permission of an adult, both his parents or other vehicle owners. The legal protection of children as perpetrators in traffic accidents has not been fulfilled as in the Supreme Court Decree No. 1029 K / Pid.Sus / 2015, the vehicle owner who surrendered his vehicle (car) was only made a witness in a traffic accident that resulted in a victim died, and the child became the sole culprit.Keywords: Liability; Criminal; Motorized Vehicles; Children.